Preparation of Plasma Active Water and Its Effect on Storage Quality of Fresh Beef - Wenlong HONG; Zhaoqi DAI; Jianying ZHAO; Ji LUO; Zhaobin WANG (Shipin gongye ke-ji)
To study the effects of plasma active water (PAW) spray treatment on quality characteristics of fresh beef during storage, PAW was prepared by dielectric barrier plasma (DBD-CP). The concentration changes of specific reactive oxygen species and reactive nitrogen species in PAW prepared with different treatment time were detected. And the effects of PAW on fresh-keeping quality of fresh beef during storage were evaluated by analyzing the changes of microbial quantity, a* value, pH and total volatile base nitrogen (TVB-N) value during storage (4 ℃, stored for 7 d). The results showed that with the increase of DBD treatment time, the concentration of reactive oxygen species in PAW was significantly increased (P<0.05). However, after the treatment time exceeded 5 min, the nitrite concentration decreased, possibly because the increase of H2O2 concentration limited the generation and transformation of nitrite. It was found that PAW treatment could significantly inhibit the total number of colonies, the growth of Escherichia coli and pseudomonas in fresh beef. Among them, PAW group prepared in 4, 5 and 6 min (T4, T5, T6) group had the best antibacterial performance. After 7 d of storage, the total number of colonies decreased by 1.58, 1.72 and 1.82 lg CFU/g, the total number of Escherichia coli decreased by 0.59, 0.60 and 0.72 lg CFU/g, and the total number of pseudomonas decreased by 0.88, 1.03 and 1.10 lg CFU/g, respectively. In addition, PAW could slow down the increase of pH and TVB-N of meat products, and the pH and TVB-N values in T4~T6 group were significantly lower than those in CK group during storage (P<0.05). However, due to the high degree of oxidation, a* value of meat in T5 and T6 groups was significantly lower than that in CK group during the whole storage period (P<0.05), while a* value in T4 group increased at the late storage stage, and was significantly higher than that in CK group after the 5th day (P<0.05). Comprehensive consideration, T4 group could not only effectively inhibit the reproduction of microorganisms, but also delay the deterioration of physical and chemical indexes and a* value, that had a good fresh-keeping effect. This study can provide reference for the application of PAW in fresh beef storage and preservation.